Long term visual outcome of radiated uveal melanomas in eyes eligible for randomisation to enucleation versus brachytherapy. Issue 2 (February 1996) - Char, D H; Kroll, S; Quivey, J M; Castro, J
Abstract : AIMS: To determine the long term visual outcome of patients who were eligible for randomisation to enucleation versus brachytherapy in a US collaborative ocular melanoma study (COMS) but were treated with either helium ion or 125I radioactive plaque therapy. METHOD: A retrospective analysis was performed of 426 ciliochoroidal melanomas that met COMS inclusion criteria for randomisation to enucleation versus radioactive plaque but were treated with either helium ions or 125I brachytherapy. RESULTS: At 3 years 36.0% of eyes had 6/12 or better visual acuity. The length of visual retention was most dependent on tumour thickness, tumour location with respect to the optic nerve, fovea, or ciliary body, and patient age. In addition to these factors, the retention of 6/12 visual acuity and the time to 6/120 visual acuity were dependent on the preoperative visual acuity. The risk of visual loss was greatest immediately after treatment and decreased with time. The 5 year actuarial metastatic rate was approximately 13%. Patients at the greatest risk of post-radiation visual loss had significantly greater risk of tumour related mortality. CONCLUSIONS: Some patients who would have been eligible for randomisation to either enucleation or radioactive plaque therapy can be irradiated with retention of excellent vision.